Regulation of Workplace Sexual Harassment in Vietnam a Comparative Analysis with Australia - Thang Chien Nguyen; Yen Thi Hai Doan; Vinh The Luong; Duong Bach Nguyen (BESTUUR, 2025)
Workplace sexual harassment presents a systemic challenge to labour governance, human dignity, and equality at work. This research examines the regulation of workplace sexual harassment in Vietnam through a comparative legal analysis with the Australian approach, which emphasizes preventive and risk-based regulation. The study applies a socio-legal research design that integrates doctrinal legal analysis, functional comparative methodology, and institutional design theory to assess the legal scope of workplace sexual harassment, employers’ obligations, and enforcement and monitoring mechanisms. The findings demonstrate, first, that Vietnamese law formally recognizes workplace sexual harassment but relies primarily on reactive regulatory mechanisms, enumerative legal definitions, internal disciplinary processes, and victim-initiated enforcement. Second, the Australian regulatory approach conceptualizes sexual harassment as a systemic workplace risk and imposes proactive preventive obligations on employers, supported by independent oversight. These differences create a structural enforcement gap in Vietnam, where individual workers continue to bear the principal responsibility for prevention and enforcement. This research concludes that reform of Vietnamese law requires a transition toward a preventive regulatory framework that emphasizes organizational accountability, risk management, and proactive enforcement to ensure effective workplace protection.